Hófvz Tartarar secundum quosdam: сведения о татарах в исландских анналах - Jackson T.N. (Золотоордынское обозрение)
Abstract: Research objective: The purpose of this study is to collect, translate and comment on the information about Tatars contained in Icelandic annals. Research materials: Icelandic annals are amply published but scarcely studied. There are ten medieval Icelandic annals. The general view is that the annals began to be written in Iceland at the end of the thirteenth century. From this time onward, annual entries appear, while texts relating to earlier events go back to one common redaction, much of the information of which is reproduced in each of the existing annals. All of them have the same chronological system and common sources. Results and novelty of the research: Such a study has never been carried out before. The author studies in good detail ten entries from 1202 to 1398, including references to Tatars. The analysis demonstrates that these data permeate the annals in different ways: some references owe their appearance to the acquaintance of the annalists with the works of European chronicle writers, some go back to oral information spread in Icelandic-Norwegian clerical circles, some are a result of rumors circulated in Europe and brought to the Scandinavian North by pilgrims returning from Rome, and some were invented by annalists themselves. Nevertheless, these ten mentions relate to very significant moments in the Mongol interaction with the Christian West: the beginning of the Tatar expansion in 1202, the conquest of Hungary by Tatars in 1241, the presence of Mongol ambassadors at the Second Lyon Council of 1274, the conquest of the Holy Land by the Mongols in 1299, and a number of others.